1991
DOI: 10.1128/mcb.11.5.2425
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity at position 37 in human epidermal growth factor is not obligatory for activity.

Abstract: The third disulfide loop (amino acids 33 to 42) of human epidermal growth factor (hEGF) encompasses the region of highest amino acid conservation among all of the EGF-like family of molecules. The importance of some of these highly conserved residues for the maintenance of biological activity, especially the aromatic amino acid tyrosine at position 37, has until now been considered essential on the basis of previous studies with the EGF-like molecule transforming growth factor alpha. Variants at the Tyr-37 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…When the mitogenic potencies of the H16 mutants are compared to that of wild-type hEGF, it appears that survival may be governed by kinetically controlled events not easily correlated with receptor binding affinities determined at equilibrium. Similar conclusions have been reached in studies where the metabolic activity/viability of cell populations in response to genetically engineered EGF or TGF␣ has been assessed by 3 H-TdR [Engler et al, 1991] and 125 I-UdR [Puddicombe et al, 1996] uptake into DNA.…”
Section: Discussionsupporting
confidence: 74%
“…When the mitogenic potencies of the H16 mutants are compared to that of wild-type hEGF, it appears that survival may be governed by kinetically controlled events not easily correlated with receptor binding affinities determined at equilibrium. Similar conclusions have been reached in studies where the metabolic activity/viability of cell populations in response to genetically engineered EGF or TGF␣ has been assessed by 3 H-TdR [Engler et al, 1991] and 125 I-UdR [Puddicombe et al, 1996] uptake into DNA.…”
Section: Discussionsupporting
confidence: 74%
“…Site-directed mutagenesis of Tyr-38 in TGF-␣ and Tyr-37 in EGF apparently gives conflicting results for the significance of this residue in the receptor interaction since it was shown to be nonessential in EGF (38) and essential in TGF-␣ (16). This conflict may be the consequence of a different mechanism or site of binding with the two ligands; however, our NOE data indicate that if mutation of this residue precludes binding of TGF-␣, then it does so by altering the ligand conformation and thus probably does not contribute directly to the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…3C), is the most highly conserved region in the EGF repeat, with invariant residues Gly-36, Tyr-37, Gly-39, and Arg-41. The predicted spi protein differs from h u m a n EGF in loop C with a conservative Tyr ~ Phe change at position 37; recent work has shown that this substitution in h u m a n EGF has little or no effect on biological activity of the protein (Engler et al 1991 ). In addition, spi protein shows conservation of residues Tyr/Phe-13, Leu-15, and Arg-41, postulated to lie at the interface of the receptor and growth factor (for review, see Campbell et al 1990) and has a conservative Leu ~ Ile change at position 47.…”
Section: The Spi Gene Encodes a Putative Egf-like Growth Factormentioning
confidence: 98%